Characterization of the microaerophilic, bacteriochlorophyll a-containing bacterium Gemmatimonas phototrophica sp. nov., and emended descriptions of the genus Gemmatimonas and Gemmatimonas aurantiaca - Zeng, Yonghui; Selyanin, Vadim; Lukeš, Martin; Dean, Jason; Kaftan, David; Feng, Fuying; Koblížek, Michal (International journal of systematic and evolutionary microbiology, 2015)
A red-pigmented, bacteriochlorophyll (BChl) a-producing strain, AP64T, was isolated previously from the freshwater Swan Lake located in the western Gobi Desert. Based on its 16S rRNA gene sequence identity (96.1%) to the type strain Gemmatimonas aurantiaca T-27T, the new isolate was tentatively classified as a member of the bacterial phylum Gemmatimonadetes. Here, we report its formal description and polyphasic characterization. Strain AP64T grew best on agar media under 9.8-15.2% atmospheric oxygen. The cells were rods, dividing by symmetrical or asymmetrical binary fission. Budding structures were also observed. Its genomic DNA G+C content was 64.4% (from the draft genome sequence). Phylogenetic analysis based on the 16S rRNA gene sequence clearly separated AP64T from related species. Its genotypic differentiation from phylogenetically close relatives was further supported by performing in silico DNA-DNA hybridization and calculating average nucleotide identity, whereas the high percentage (67.3%) of shared conserved proteins between strain AP64T and Gemmatimonas aurantiaca T-27T supports the classification of the two strains into the same genus. Strain AP64T contained C16 : 1, C14 : 1 and C18 : 1ω9c as predominant fatty acids. The main respiratory quinone was menaquinone 8 (MK-8). The most distinctive feature of strain AP64T was the presence of fully functional purple bacterial photosynthetic reaction centres. The main CO2-fixation pathways were absent. Strain AP64T was capable of growth and BChl production in constant darkness. Thus, strain AP64T is a facultatively photoheterotrophic organism. It represents a novel species of the genus Gemmatimonas, for which the name Gemmatimonasphototrophica sp. nov. is proposed. The type strain is AP64T ( = DSM 29774T = MCCC 1K00454T). Emended descriptions of the genus Gemmatimonas and Gemmatimonas aurantiaca are also provided.
Keywords: zastoupení bazí; China; sekvence nukleotidů; vitamin K 2; fylogeneze; techniky typizace bakterií; RNA, Ribosomal, 16S; Lakes; Vitamin K 2; mastné kyseliny; Sequence Analysis, DNA; Phylogeny; sekvenční analýza DNA; Bacteria; molekulární sekvence - údaje; Bacteriochlorophyll A; sladká voda; Fresh Water; Fatty Acids; hybridizace nukleových kyselin; jezera; DNA, Bacterial; Desert Climate; DNA bakterií; bakteriochlorofyl A; Base Composition; pouštní klima; RNA ribozomální 16S; Bacterial Typing Techniques; Molecular Sequence Data; Base Sequence; Čína; Nucleic Acid Hybridization